Carbon isotope ratios of selected volatiles in Citrus sinensis and in orange‐flavoured food. (30th December 2014) - Schipilliti, Luisa; Bonaccorsi, Ivana; Cotroneo, Antonella; Dugo, Paola; Mondello, Luigi
Abstract BACKGROUND Twenty genuine samples of industrially cold‐pressed sweet orange essential oils, were analysed by gas chromatography–combustion‐isotope ratio mass spectrometry to determine the values of the carbon isotope ratios (δ13CVPDB) of selected volatiles and assess the corresponding range of authenticity. Successively, four commercial orange‐flavoured products were analysed under identical conditions to evaluate the authenticity of the orange flavour. The samples were extracted by solid‐phase microextraction under optimised conditions. The evaluation was performed by using an internal standard procedure to neglect the contribution due to the original environment to the isotopic abundance of 13C. The composition of the volatile fraction of the essential oils and of the flavoured products was determined by gas chromatography coupled to mass spectrometry with linear retention indices, and by gas chromatography with a flame ionisation detector. RESULTS The δ13CVPDB values of seven secondary metabolites determined here were successfully used to characterise genuine orange essential oil. These values were used to evaluate the quality of orange‐flavoured products, revealing the presence of compounds of different origin, not compatible with the values of genuine orange secondary metabolites. CONCLUSIONS This study provides the range of authenticity of δ13CVPDB of seven different secondary metabolites in sweet orange genuine essential oil, useful for evaluating the genuineness of orange flavour. In accord with a previous study on different essential oils, the values determined here can be successfully applied for the evaluation of a large number of flavoured food stuffs and correlated with their origins. © 2014 Society of Chemical Industry